دراسة مستوى التلوث الجرثومي وتقييم فعالية إجراءات التعقيم والتطهير المتبعة في مواقع العمل في عيادات كلية طب الأسنان في جامعة تشرين - الغنطاوي, يحيى; خليل, علي; نور الله, عبد الوهاب (Latakia University Journal -Medical Sciences Series, 2015)
الهدف من هذه الدراسة هو تقييم التلوث الجرثومي وفعالية ضبط انتقال الانتان في عيادات كلية طب الأسنان في جامعة تشرين. تم تقييم التلوث الجرثومي للسطوح في 4 عيادات للمرحلة الجامعية و 4 عيادات لمرحلة الدراسات العليا. أخذت المسحات الجرثومية في هذه الدراسة من مواقع متنوعة من وبجوار الجهاز السني في هذه العيادات. تمت دراسة التلوث الجرثومي بتسجيل شكل المستعمرات الجرثومية على مزارعها، الفحص للعينات المصبوغة بصبغة غرام بالمجهر الضوئي، وكذلك تحديد الخصائص الكيماحيوية للمستعمرات المعزولة و ذلك باستخدام البرتوكولات الجرثومية القياسية. أظهرت النتائج أن التلوث الجرثومي حاصل في كل العيادات السنية. كما أن مستوى التراكم الجرثومي على السطوح المدروسة لم يتغير كل الوقت. أظهر التحليل الجرثومي أن 100% من الكراسي السنية ملوثة بالجراثيم. كما أظهر أن 77% من المسحات احتوت على مكورات إيجابية الغرام، مما يدل على أن هذه الجراثيم هي المجموعة الأساسية الملوثة للعيادة السنية. تسلط الدراسة الحالية الضوء على حقيقة أن كل مواقع العيادات السنية تشكل مصدراً محتملاً لانتقال الجراثيم. تؤكد نتائج هذه الدراسة على عدم كفاية الإجراءات المتبعة في ضبط انتقال الانتان وخاصة البند المتعلق بتطهير السطوح، كما تؤكد على ضرورة التطبيق الصارم لإجراءات ضبط انتقال الانتان، وذلك لمنع انتقال التلوث الجرثومي من الكرسي السني أثناء العمل في العيادات السنية. The present study assessed the bacterial contamination and the efficacy of control infection protocol in clinica=l practices in Faculty of Dentistry in Tishreen university. An evaluation of surface bacterial contamination in 4 laboratory of clinical dental practices was for undergraduate stage and 4 laboratory of clinical practices for postgraduate stage. The samples for the study were taken from various sites from and beside dental-chair. The bacterial contamination was studied by observing and recording the colony morphology on the culture plates, Gram's staining with light microscopic screening of the slides, and the biochemical characterization of the isolates using standard bacteriology protocols.The findings showed bacterial contamination in all the surfaces in the laboratory of dental practices. The level of bacterial accumulation on examined surfaces did not change over time. bacteriological analysis showed that 100% of dental chair had bacterial contamination. More the 77% of collected swabs showed Gram-positive cocci, making it the major bacterial group contaminating the surfaces of dental-chair in the dental operatory. The presented study highlights the fact that all sites of dental practice is a potential source of cross infection. The results of this study mandate a strict audit process and protocols to be set in place for preventing cross-contamination from the dental chair in a dental operatory.